2019
DOI: 10.7759/cureus.4982
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycated Hemoglobin A1c in Determining the Severity of Coronary Artery Disease in Diabetic and Non-Diabetic Subjects in Karachi

Abstract: Introduction Coronary artery disease is the leading cause of death worldwide by incidence. Over the years, many studies have been conducted to find predictors of coronary artery disease; however, in the last few decades, the level of HbA1c in diabetics has been investigated as a potential predictor. Our study offers additional insight by investigating similar relationships in non-diabetic patients and by investigating potential predictors more comprehensively, making it the first of its kind study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…With increasing HbA1c levels, a marked increase in SYNTAX score was noted in the patients without a history of taking Statins Epidemiologic studies show that HbA1c is a cardiovascular risk factor in all kinds of individuals. [3][4][5][6][7][8][9][10] Our findings are in accordance with prior studies that demonstrated that HbA1c levels are independently associated with SYNTAX score which represents the degree of coronary atherosclerosis in non-diabetic and diabetic individuals. This association is graded, continuous, and independent of conventional major cardiovascular risk factors and history of taking cardiovascular related drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With increasing HbA1c levels, a marked increase in SYNTAX score was noted in the patients without a history of taking Statins Epidemiologic studies show that HbA1c is a cardiovascular risk factor in all kinds of individuals. [3][4][5][6][7][8][9][10] Our findings are in accordance with prior studies that demonstrated that HbA1c levels are independently associated with SYNTAX score which represents the degree of coronary atherosclerosis in non-diabetic and diabetic individuals. This association is graded, continuous, and independent of conventional major cardiovascular risk factors and history of taking cardiovascular related drugs.…”
Section: Discussionsupporting
confidence: 92%
“…There are lots of researches elaborating the effects of glycemic metabolism on CAD. 2–10 These studies show that HbA1C were correlated positively with the Severity of CAD in different groups of people, such as older patients with diabetes mellitus, 8 Type 2 Diabetes Mellitus, 7 Non-Diabetic Subjects, 4 , 6 Diabetic and Non-Diabetic Subjects, 3 , 9 PCI Patients With HbA1c 5.7% to 6.4 10 and Non-diabetic Patients with Acute Coronary Syndrome 5 . However, previous studies regarding the relationship between HbA1c and SYNTAX score just adjusted some conventional risk factor, not adjusted conventional cardiovascular drugs.…”
Section: Introductionmentioning
confidence: 92%
“…and Ul-Haque et al . [ 34 35 ] Further, the HbA1c level was positively co-related with BMI in diabetic patients ( r = 0.38; P = 0.0107) in line with the findings by Babikr et al . [ 36 ] Moreover, correlation was similar and significance between HbA1c and FBS, PPBS between both the groups ( P < 0.0001) was with a higher r-value for PPBS than the FBS in the nondiabetic group.…”
Section: Discussionsupporting
confidence: 88%